The artificial zinc finger coding gene 'Jazz' binds the utrophin promoter and activates transcription. - Corbi, N; Libri, V; Fanciulli, M; Tinsley, J; Davies, K; Passananti, C (2000)
Up-regulation of utrophin gene expression is recognized as a plausible therapeutic approach in the treatment of Duchenne muscular dystrophy (DMD). We have designed and engineered new zinc finger-based transcription factors capable of binding and activating transcription from the promoter of the dystrophin-related gene, utrophin. Using the recognition 'code' that proposes specific rules between zinc finger primary structure and potential DNA binding sites, we engineered a new gene named 'Jazz' that encodes for a three-zinc finger peptide. Jazz belongs to the Cys2-His2 zinc finger type and was engineered to target the nine base pair DNA sequence: 5'-GCT-GCT-GCG-3', present in the promoter region of both the human and mouse utrophin gene. The entire zinc finger alpha-helix region, containing the amino acid positions that are crucial for DNA binding, was specifically chosen on the basis of the contacts more frequently represented in the available list of the 'code'. Here we demonstrate that Jazz protein binds specifically to the double-stranded DNA target, with a dissociation constant of about 32 nM. Band shift and super-shift experiments confirmed the high affinity and specificity of Jazz protein for its DNA target. Moreover, we show that chimeric proteins, named Gal4-Jazz and Sp1-Jazz, are able to drive the transcription of a test gene from the human utrophin promoter.